(untitled) (International Conference on Computers in Education, 2019)
IT advancement allowed us to experience technology enhanced learning (TEL). However, a learner should implement TEL gradually, following a maturity roadmap, by paying attention to TEL characteristics. TEL covers an extensive discussion embedded in hundreds of research articles. Thus, this research explores the TEL key terms from 12 research digital libraries using the Signific ant Words approach, postulated by Luhn. The 65 key terms were then analyzed to conceive TEL characteristics. There are nine characteristics for TEL maturity, discussing TEL coverage in facilitating formal-informal learning and various alternatives of learning methods, applying state-of-art technology along with social media and learning management system, and also improving the learning experience and the learning environment to enable self-directed learning. This result may become a foundation to formulate TEL maturity measures.